Exploring the diversity of the root-associated microbiome of Ilex paraguariensis St. Hil. (Yerba Mate) - Bergottini, Veronica M.; Hervé, Vincent; Sosa, Domingo Alberto; Otegui, Mónica B.; Zapata, Pedro Darío; Junier, Pilar (2018)
Ilex paraguariensis St. Hil. (Yerba Mate) is an important crop for which a decrease in yields associated to unsustainable agricultural practices is well documented. The aim of this study is to investigate the diversity of bacteria and fungi inhabiting roots of Yerba Mate. This is an important pre-requisite for the use of microorganisms inhabiting roots to modulate plant nutrition and health as an ecologically friendly agricultural alternative for this crop. The diversity of the root-associated microbiome from eleven plantations with different agricultural practices was analyzed by high throughput sequencing of the 16S rRNA gene as a bacterial marker, whereas the fungal communities were targeted by amplifying the ITS region of the ribosomal RNA gene cluster. A comparison of the bacterial and fungal communities between plantation sites and cultivation practices was made to address the major factors contributing to the structure of the root microbiome of this crop. Operational taxonomic units (OTUs) related to well-known plant growth promoting bacteria such as Burkholderia, Bradyrhizobium, Weissella, Enterobacter and Rhizobium were detected. Those might constitute targets for future enrichment efforts of plant growth promoting clades. The analysis of the fungal community composition demonstrated that arbuscular mycorrhizae colonize Yerba Mate roots, and that the frequency of this group is favored in degraded soils. The detection of other groups harboring potential phytopathogens might help to broaden the understanding of the ailments affecting this crop. This study provides the first description of the root-associated microbiome of Yerba Mate and constitutes a stepping-stone towards harnessing the role of microbes in the sustainable cultivation of this crop.